Bullying Prevention Among Students in Bengkulu City: A Study of Positive Law and Islamic Law Approaches - Helda Rahmasari; Herlambang Unib; Randy Pradityo; Ardika Sari; Risna Karinda (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
Bullying is a form of violence against children that has become increasingly prevalent, particularly within the school environment, which is ideally a secure space. Consequently, it is essential to conduct further studies on the efforts to combat bullying among students in Bengkulu City, with the aim of identifying the strategies and measures implemented to prevent or manage instances of bullying across all demographics, as well as understanding the obstacles encountered in addressing bullying in Bengkulu City. To address these issues, the researcher employs an empirical legal research methodology, adopting a sociological approach to law in action, utilising both primary and secondary data. Based on research conducted in schools, as well as with the DP3AP2KB, PUPA, and Polresta Bengkulu, it is evident that initiatives to combat bullying have been established. However, these efforts have not yet been fully realised and are hindered by several factors, one of which stems from parental involvement. The schools participating in this research have made efforts to address bullying, such as conducting socialisation campaigns, forming anti- bullying teams, and other related activities; however, these initiatives have not yet been executed to their full potential. This research contributes to the existing body of knowledge by mapping out the current anti-bullying strategies and identifying the practical and institutional challenges faced in their implementation. The findings are expected to inform policymakers, educators, and legal practitioners in developing more effective and collaborative interventions to prevent bullying in school environments